A computational fluid dynamics study of the near surface wind patterns over a desert dune and the effect on seed dispersion - Joubert, Eugene Christiaan (Stellenbosch : Stellenbosch University, 2010)
Thesis (MScEng)--Stellenbosch University, 2010.